2015
DOI: 10.3389/fnut.2015.00010
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting base excision repair to improve therapeutic approaches for pancreatic cancer

Abstract: Pancreatic ductal adenocarcinoma (PDA) is a highly chemoresistant and metastatic disease with a dismal 5-year survival rate of 6%. More effective therapeutic targets and approaches are urgently needed to tackle this devastating disease. The base excision repair (BER) pathway has been identified as a predictor of therapeutic response, prognostic factor, and therapeutic target in a variety of cancers. This review will discuss our current understanding of BER in PDA and its potential to improve PDA treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 137 publications
(126 reference statements)
0
20
0
Order By: Relevance
“…Apurinic/Apyrimidinic Endonuclease/Redox Factor-1 (APE1/Ref-1) is a multifunctional protein that is involved in responses to oxidative stress, acting on both oxidative and alkylative DNA damage (via its endonuclease activity in base excision repair) (1719) and augmenting activity of various transcription factors (via its redox signaling) (2023), as well as contributing to clearance of RNA with damaged bases (24). APE1/Ref-1 expression and redox activity are increased in PDAC tissue, and its upregulation increases tumor cell migration, proliferation, and survival (17, 23).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apurinic/Apyrimidinic Endonuclease/Redox Factor-1 (APE1/Ref-1) is a multifunctional protein that is involved in responses to oxidative stress, acting on both oxidative and alkylative DNA damage (via its endonuclease activity in base excision repair) (1719) and augmenting activity of various transcription factors (via its redox signaling) (2023), as well as contributing to clearance of RNA with damaged bases (24). APE1/Ref-1 expression and redox activity are increased in PDAC tissue, and its upregulation increases tumor cell migration, proliferation, and survival (17, 23).…”
Section: Introductionmentioning
confidence: 99%
“…APE1/Ref-1 expression and redox activity are increased in PDAC tissue, and its upregulation increases tumor cell migration, proliferation, and survival (17, 23). We previously demonstrated that APE1/Ref-1 redox activity regulates several transcription factors involved in pancreatic cancer signaling, including HIF-1α, as well as STAT3, and NFκB (20, 21).…”
Section: Introductionmentioning
confidence: 99%
“…APE1 expression is increased in several cancers such as pancreatic (Jiang et al ., 2010), prostate (Kelley et al ., 2001), cervical (Xu et al ., 1997), gliomas (Bobola et al ., 2004), lung (Yoo et al ., 2008), bladder (Shin et al ., 2015), colon (Lou et al ., 2014), and ovarian cancers (Al‐Attar et al ., 2010; Zhang et al ., 2009), and this increase is associated with resistance to radiation and chemotherapy, leading to poorer patient prognosis (Sharbeen et al ., 2015). Based on its involvement in cancer, and its regulation of several transcription factors associated with cancer‐related pathways, APE1 has become a prime target for anticancer therapies (Fishel and Kelley, 2007; Kelley et al ., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…DNA bases by flap-endonuclease (FEN1) and PCNA (Sharbeen et al, 2015;Sokhansanj et al, 2002). In our results, significant up-regulation of osfen1 gene and ospcna in shoots was detected, where in roots it was contrary.…”
Section: Discussionmentioning
confidence: 52%